2019
DOI: 10.1002/prp2.546
|View full text |Cite
|
Sign up to set email alerts
|

Rezafungin treatment in mouse models of invasive candidiasis and aspergillosis: Insights on the PK/PD pharmacometrics of rezafungin efficacy

Abstract: Rezafungin acetate is a novel echinocandin in clinical development for prevention and treatment of invasive fungal infections. Rezafungin is differentiated by a pharmacokinetic/pharmacodynamic (PK/PD) profile that includes a long half‐life allowing once‐weekly administration, front‐loaded plasma drug exposures associated with antifungal efficacy, and penetration into deep‐seated infections, such as intra‐abdominal abscesses. In this series of in vivo studies, rezafungin demonstrated efficacy in the treatment o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 31 publications
0
31
0
Order By: Relevance
“…Ever since the early stage of the in vitro characterization of rezafungin, an increasing body of evidence has established that rezafungin is effective in treating invasive infections due to multiple fungal species, including Candida spp., Aspergillus spp. and Pneumocystis spp., in animal models [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ]. Except for one study using a rabbit model to assess treatment efficacy for Candida endophthalmitis [ 21 ] and another one examining burden reduction in an intra-abdominal candidiasis mouse model [ 11 ], all other studies used immunocompromised mice to establish invasive infections due to different pathogens.…”
Section: In Vivo Effectivenessmentioning
confidence: 99%
“…Ever since the early stage of the in vitro characterization of rezafungin, an increasing body of evidence has established that rezafungin is effective in treating invasive infections due to multiple fungal species, including Candida spp., Aspergillus spp. and Pneumocystis spp., in animal models [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ]. Except for one study using a rabbit model to assess treatment efficacy for Candida endophthalmitis [ 21 ] and another one examining burden reduction in an intra-abdominal candidiasis mouse model [ 11 ], all other studies used immunocompromised mice to establish invasive infections due to different pathogens.…”
Section: In Vivo Effectivenessmentioning
confidence: 99%
“…Drug levels in the CSF and eye compartments are predicted to be low, 27,157 but brain parenchymal concentrations in animal studies are higher than those observed in serum. 29,76,159 In a recent study in mice, Wiederhold and colleagues found ISA concentrations in brain tissue ranging from undetectable levels to 17.3 µg/g (Table 2) in different dosage groups, and the brain tissue/plasma ratio was high (approximately 1.35) for each dose tested. 76 Other study also found ISA at high concentrations in the brain of the studied mice.…”
Section: Tri a Zo Le Smentioning
confidence: 96%
“…REZ showed potent activity for the prevention of infections caused by Aspergillus, Candida and Pneumocystis in bone marrow transplant patients, and a prophylaxis trial is currently in planning stages 180‐184 . It has long‐acting pharmacokinetics (half‐life > 130 hours) and stability, supporting high plasma drug exposures and a longer dosing interval 28,29,181,185 . The great advantage of REZ is that it has exceptional chemical stability, allowing for topical application and higher aqueous solubility, compared to other echinocandins 179 …”
Section: Promising Antifungal Candidates Under Development On Phase Imentioning
confidence: 99%
See 1 more Smart Citation
“…Rezafungin showed in vivo efficacy in a neutropenic murine model with disseminated infection caused by A. fumigatus (ATCC 13073), providing 10-day survival rates with a one-time dose of 2 mg/kg [ 66 ].…”
Section: Improving Existing Antifungalsmentioning
confidence: 99%